ANALISIS BIBLIOMETRIK: TREN PENELITIAN PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN IPS - Trapsila Siwi Hutami; Prasetyo Adi Nugroho; Fahimatul Anis (STKIP Singkawang, 2023)
This research aims to determine research trends on the influence of the Problem Based Learning model on critical thinking skills in social studies learning through bibliometric analysis. The research method used is a literature study with a bibliometric analysis approach where existing data can become useful information. The analysis used is a descriptive analysis using indexed journal article data sources on Google Scholar. The results of research from 2019-2023 indicate four main clusters of discussion on the impact of Problem Based Learning model on critical thinking skills in social studies, with a predominant focus on students as learning subjects. Bibliometric data shows that in 2023 there will still be little research on Google Scholar that discusses this theme so it could be an opportunity for future researchers to examine the influence of the Problem Based Learning model on critical thinking skills at various levels of education.